Pulmonary Embolism Secondary to Catheter-Related Thrombosis - Poenou, Géraldine; Toledano, Emmanuel; Meklhoufi, Yosra; Helfer, Helene; Mahe, Isabelle (Archives of Clinical and Medical Case Reports, 2021)
A central venous catheter is a device used for chemotherapy. Catheters are at high risk for local venous thrombosis. Once a catheter-related thrombosis is formed, the risk of concomitant pulmonary embolism is regularly underestimated. A 58-year-old man with a non-metastatic pulmonary cancer reported a right-side cervical pain and episodes of hemoptysis. A thrombosis of the right internal vein was detected with compressive ultrasound imaging. Because of the presence of abnormal respiratory signs, a CT scan was performed that confirmed a pulmonary embolism. A catheter related thrombosis is associated with a number of clinically relevant complications, including catheter dysfunction, recurrent deep venous thrombosis, post thrombotic syndrome, anticoagulation-associated bleeding and pulmonary embolism. The risk of fatal pulmonary embolism should not be missed.